Curso básico de manutenção de climatizadores domésticos para alunos de ensino de jovens e adultos do município de Tucuruí - TEIXEIRA, Thales de Souza (2022)
This work is the development of a basic course in the area of climate control, focusing mainly on the air conditioning equipment. In Tucuruí region, the ambient air conditioning becomes a necessity due to the high temperatures and humidities recorded, making it necessary to use air conditioners for thermal comfort of people. Keeping in mind that these devices need regular maintenance, refrigeration companies see the need for a skilled, qualified labor for the realization of their services. The GPRAC (Research Group in Refrigeration and Air Conditioning), made possible the realization of a extension course facing this sector of engineering, targeting public school education for youth and adults (EJA), with the intention of not only convey technical knowledge, but also to encourage these students to pursue an academic career in the near future.